HUBUNGAN ASUPAN GARAM, ANEMIA, DAN KADAR IODIUM URINE PADA IBU HAMIL - SUPRAPTI, EKA; ADRIANA, VIVI; SUMIATI, SUMIATI; NURPADILA, NURPADILA (Jurnal Kesehatan Marendeng, 2025)
Background: Iodine deficiency and anemia remain major nutritional problems among pregnant women in Indonesia, with potentially serious consequences for maternal health and fetal development. Both conditions increase the risk of complications during pregnancy and delivery, while also threatening the optimal growth of the fetus. Iodized salt is recognized as one of the main dietary sources of iodine, therefore monitoring iodized salt consumption together with urinary iodine levels is essential to ensure adequacy and prevent deficiency-related disorders. Objective: This study aimed to analyze the relationship between iodized salt consumption and anemia status with urinary iodine levels among pregnant women in the working area of Samata Health Center. Methods: This analytic observational study applied a cross-sectional design conducted from May to August 2025 and involved 48 pregnant women selected using purposive sampling. Respondent characteristics included age, education, husband’s occupation, mother’s occupation, parity, knowledge of iodine, and knowledge of micronutrients, which were collected through structured questionnaires. Laboratory examinations consisted of measuring iodine concentration in household salt by titrimetric method, hemoglobin concentration with Hemocue Hb 301, and urinary iodine concentration using spectrophotometry at Parahita Laboratory Makassar. Data were analyzed univariately to describe distributions, bivariately using the Chi-Square test, and multivariately with logistic regression at a significance level of p<0.05. Results: The study revealed that most respondents consumed iodized salt, although a proportion still used salt with insufficient iodine content. A considerable number of pregnant women experienced anemia with hemoglobin levels below 11 g/dl. Bivariate analysis showed significant associations between salt iodine concentration (p=0.030) and hemoglobin levels (p=0.029) with urinary iodine levels, while multivariate analysis confirmed iodized salt consumption as the most influential factor